Acinetobacter geminorum sp. nov., isolated from human throat swabs. Issue 10 (11th October 2021) - Wolf, Sophia; Barth-Jakschic, Elisabeth; Birkle, Karolin; Bader, Baris; Marschal, Matthias; Liese, Jan; Peter, Silke; Oberhettinger, Philipp
Abstract : Two isolates of a non-fermenting, Gram-negative bacterial strain were cultured from two throat swabs that were taken from a pair of twins during routine microbiological surveillance screening. As these isolates could not be unambiguously identified using routine diagnostic methods, whole genome sequencing was performed followed by phylogenetic analysis based on the rpoB gene sequence and by whole genome datasets. The two strains compose a separate branch within the clade formed by the Acinetobacter calcoaceticus–baumannii (ACB) complex with Acinetobacter pittii CIP 70.29 T as the most closely related species. The average nucleotide identity compared to all other species of the ACB complex was below 94.2% and digital DNA–DNA hybridization values were less than 60%. Biochemical characteristics confirm affiliation to the ACB complex with some specific phenotypic differences. As a result of the described data, a new Acinetobacter species is introduced, for which the name Acinetobacter geminorum sp. nov. is proposed. The type strain is J00019 T with a G+C DNA content of 38.8 mol% and it is deposited in the DSMZ Germany (DSM 111094 T ) and CCUG Sweden (CCUG 74625 T ).